Being La Dominicana : Race and Identity in the Visual Culture of Santo Domingo - Quinn, Rachel Afi (Book collections on Project MUSE., 2021)
"This book investigates the ways Dominican visual culture portrays Dominican women and how women represent themselves in their own creative endeavors in response to existing stereotypes. Delving into the dynamic realities and uniquely racialized gendered experiences of women in Santo Domingo, Quinn reveals the way racial ambiguity and color hierarchy work to shape experiences of identity and subjectivity in the Dominican Republic. She merges analyses of context and interviews with young Dominican women to offer rare insights into a Caribbean society in which the tourist industry and popular media reward, and rely upon, the ability of Dominican women to transform themselves to perform gender, race, and class"--